Dysmenorrhea among University Health Science Students, Northern Ethiopia: Impact and Associated Factors - Yesuf, Teshager Aklilu; Eshete, Nigist Assefa; Sisay, Eskinder Ayalew (International Journal of Reproductive Medicine, 2018)
Background. It is estimated that more than half of all women in adolescence age suffer from dysmenorrhea and it often interferes with their daily physical and emotional aspects. It is the leading cause of short-term school absenteeism and is associated with a negative impact on academic and daily activities. Objectives. To investigate impacts of dysmenorrhea, factors associated with it, and its self-management strategies used by health science students. Methods. A cross-sectional institution based study was conducted among 246 Mekelle University health science students selected by stratified random sampling technique. Data were collected using self-administered semistructured questionnaire. Data were analyzed using SPSS 16. Results. The prevalence of dysmenorrhea was 71.8%. Participants who had long menstrual cycle interval, long menses flows, and positive family history and who were alcohol users were more likely to had dysmenorrhea. Participants reported that 28.6% feel depressed, 16.2% are absent from class, and 22.9% had poor personal relationship due to dysmenorrhea and 78.2% of them practiced self-medication. Conclusion. Dysmenorrhea is common among Mekelle University health science students and it is major problem representing the cause of feeling depressed, poor personal relationship, and class absenteeism. Majority of the study participants used self-medication to treat dysmenorrhea.